2022
DOI: 10.1155/2022/1203514
|View full text |Cite
|
Sign up to set email alerts
|

Water and Latrine Services and Associated Factors among Residents of Negele Town, Southeast Ethiopia: A Cross‐Sectional Study

Abstract: Background. Access to at least a basic water service, improved sanitation, and hygiene contribute to the human health and socioeconomic development of a country. This study was conducted to assess the water and latrine service coverage and related factors among dwellers of Negele town, southeast Ethiopia. Method. Two Kebeles (small administrative units) were randomly selected from each of the three zones of the town to collect data via questionnaires from randomly selected household heads (380), interviews of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, inadequate space and loose soils which do not support the construction of strong toilets has been reported in different regions. In Ethiopia, [19] established that shortage of space to construct toilets facilitated the practice of defecating in bushes. As well, participants in another study by [20] in Ethiopia reported that, among the obstacles for constructing household toilets was inadequate space for the construction of sanitation facilities.…”
Section: Ephirical Reviewmentioning
confidence: 99%
“…However, inadequate space and loose soils which do not support the construction of strong toilets has been reported in different regions. In Ethiopia, [19] established that shortage of space to construct toilets facilitated the practice of defecating in bushes. As well, participants in another study by [20] in Ethiopia reported that, among the obstacles for constructing household toilets was inadequate space for the construction of sanitation facilities.…”
Section: Ephirical Reviewmentioning
confidence: 99%
“…For instance, 87% of the households in Jimma town have used unsafe sanitation services [ 11 ]. 45% of available latrine facilities are poor in hygiene, and the pipelines are poor in function in Negele town [ 12 ]. In Gondar town, 67% of the households have an unimproved sanitation status, and 51.7% of households have poor hygiene practices [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different individual and community-level factors may represent associated factors for sanitation service access. Family size, the sex of the household head, occupation, income, wealth status, toilet age [ 11 ], and educational and marital status [ 12 ] may be associated factors for sanitation service access.…”
Section: Introductionmentioning
confidence: 99%